An Authentic Material Comic to Improve Students’ Vocabulary Mastery - Satriani; Bahri, Syamsul; Amiruddin; Reski, Muhammad; Ahmad, Gufran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The goal of this study was to see if there was a substantial improvement in students' vocabulary proficiency after they were taught vocabulary using actual material. In this study, the pre-experimental design was used with a one-group pretest-posttest design. The first semester of English instruction at IAI As'adiyah Sengkang in the academic year 2020/2021 served as the study's sample. Simple random sampling was utilized in this study. A total of 15 students were used as samples. Written tests were employed as part of the study instrument. The utilization of real resources significantly improved students' vocabulary mastery, according to the findings of this study. The t-test result of -20,911 with a significance of 0.00 < 0.05 and a degree of freedom (n-1) of 28 showed this. As a result, the null hypothesis (H0) has been rejected, whereas the alternative hypothesis (H1) has been accepted.